PEMAHAMAN FUNGSI PAJAK DAN TINGKAT PENGHASILAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI KASUS PADA WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN PATI) - Putri Veronika; Kasidi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The research aims to determine and analyze influences tax understanding of motor vehicle taxpayer comlpliance and effect of income level on compliance motor vehicle taxpayers. The population in this research is all motor vehicle taxpayers in Pati Regency which is registered with SAMSAT Pati. The research was carried out randomly sampling using purposive sampling technique, a sample was obtained as many as 100 data. The analysis technique used is multiple linear regression.The research results can be summarized as follows :Understanding the tax function is nothas a positive and significant effect on vehicle tax compliance motorized, and Income level has a positive and significant effect onmotor vehicle tax compliance.